2016
DOI: 10.1155/2016/9627258
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Contributions to Cognitive Impairment and Treatments with Traditional Chinese Medicine

Abstract: The prevalence of cognitive impairment and dementia caused by cerebrovascular disease is likely to increase with the global aging population. Vascular contributions to cognitive impairment and dementia (VCID) is a wide spectrum term used to include a diverse heterogeneous group of cognitive syndromes with vascular factors regardless of the cause of pathogenesis. VCID ranges from mild cognitive impairment to full-blown dementia with vascular dementia (VaD) as the most severe stage. It is further complexed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 100 publications
1
17
0
Order By: Relevance
“…Previous evidence showed that the VD is treated by Wenpi Tongluo decoction and Nimodipine, the study found the level of IL-6 and TNF-α would be decreased by the combined treatments of TCM and western medicine, and there is a significantly increase of the scores of MMSE after treatments. This result was in accord with higher serum ILs were associated with poor cognitive status, including poor performance in memory and processing speed, as well as cognitive decline ( 10 , 11 ).…”
Section: Discussionsupporting
confidence: 72%
“…Previous evidence showed that the VD is treated by Wenpi Tongluo decoction and Nimodipine, the study found the level of IL-6 and TNF-α would be decreased by the combined treatments of TCM and western medicine, and there is a significantly increase of the scores of MMSE after treatments. This result was in accord with higher serum ILs were associated with poor cognitive status, including poor performance in memory and processing speed, as well as cognitive decline ( 10 , 11 ).…”
Section: Discussionsupporting
confidence: 72%
“…Gingko extract is available on market in some countries (e.g., China) as a herbal supplement named Gingium. It is intended for use in certain age-related cognitive disorders including memory impairment and it alleviates the symptoms of dementias and AD (Zhou et al, 2016a ). There are two main categories of chemical phytoconstituents likely responsible for the neuro-therapeutic potential of Gingko: terpene lactones (ginkgolides and bilobalide) and flavonoids (flavonols and flavone glycosides) (Figure 3 ; Solfrizzi and Panza, 2015 ; IARC Working Group, 2016 ).…”
Section: Selected Prominent Medicinal Plants and Plant Genera Used Fomentioning
confidence: 99%
“…The standardized Gb extract (EGb761) belongs to the most widely tested in clinical trials herbal medications worldwide for cognitive impairment, AD, and AD-related dementia (Solfrizzi and Panza, 2015 ). EGb761 affects a multitude of mechanisms associated with proper brain functions (Zhou et al, 2016a ; Figure 4 ).…”
Section: Selected Prominent Medicinal Plants and Plant Genera Used Fomentioning
confidence: 99%
“…Sailuotong (SLT) is a standardized three-herb formula Chinese herbal medicine designed for the management of VaD associated with ischemic stroke [ 8 , 9 ]. The SLT formula consists of standard extracts of specific dosages of Panax ginseng C. A. Meyer (ginseng), Gingko biloba L. (ginkgo), and Crocus sativus L. (saffron).…”
Section: Introductionmentioning
confidence: 99%